Prenatal alcohol exposure reduces mandibular calcium and phosphorus concentrations in newborn rats - Carvalho, Isabel C. S. [UNESP]; Martinelli, Carolina da S. M. [UNESP]; Milhan, Noala V. M. [UNESP]; Marchini, Adriana M. P. da S. [UNESP]; Dutra, Tamires P. [UNESP]; Souza, Daniela M. de; Rocha, Rosilene F. da [UNESP] (Nihon Univ, School Dentistry, 2016)
Previous studies suggest that prenatal alcohol exposure affects fetal bone development, including bone quality. This study evaluated the chemical composition of mandibles from newborn rats after maternal 20% alcohol consumption before and throughout gestation. Nine rats were initially distributed into three groups: an Alcohol group, Pair fed group, and Control group. The groups were fed prespecified diets for 8 weeks before and the 3 weeks during pregnancy. At age 5 days, eight newborns from each group were euthanized (total, n = 24). Using energy dispersive spectrometry, we evaluated samples of mandibles from newborns to identify changes in bone mineralization, specifically Ca and P concentrations. Ca and P concentrations were lower in the Alcohol group than in the Control and Pair-fed groups (P = 0.003 and P = 0.001, respectively). In summary, alcohol exposure before and throughout gestation reduces mandibular Ca and P concentrations in newborn rats.
Keywords: alcohol; gestation; calcium; phosphorous; mandible; rat